1992
DOI: 10.1007/bf00210745
|View full text |Cite
|
Sign up to set email alerts
|

Detection of GST1 gene deletion by the polymerase chain reaction and its possible correlation with stomach cancer in Japanese

Abstract: A homozygous gene deletion at the GST1 locus of genomic DNA isolated from peripheral blood was investigated for its relationship with several types of cancer using the polymerase chain reaction (PCR) technique. DNA samples were prepared from blood obtained from 128 healthy blood donors and 150 patients with cancer or chronic hepatitis. PCR primers were prepared based on the human cDNA sequence and the intron/exon sequences of the rat Yb2 gene. The amplified sequence between exons 5 and 6 including intron 5 sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
39
0
4

Year Published

1996
1996
2005
2005

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(46 citation statements)
references
References 12 publications
3
39
0
4
Order By: Relevance
“…This is consistent with results previously reported for smaller groups by Harada et al (1992), Zhong et al (1993) or Paradiso et al (1994) comparing null and non-null genotypes.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…This is consistent with results previously reported for smaller groups by Harada et al (1992), Zhong et al (1993) or Paradiso et al (1994) comparing null and non-null genotypes.…”
Section: Discussionsupporting
confidence: 94%
“…Zhong et al (1993) compared 225 controls and 197 breast cancer patients; Harada et al (1992) studied 84 controls and 65 patients. Ambrosone et al (1995) restricted their study to postmenopausal women: they compared 212 Caucasian patients and 282 community controls and discovered a trend towards an increased breast cancer risk among GSTM1 null post-menopausal women under 58 years of age [odds ratio (OR) = 2.44].…”
mentioning
confidence: 99%
“…Several studies have reported an independent, increased risk of gastric cancer for the GSTM1 null [7] , GSTT1 null [6] , CYP2E1 c1/c2 or c2/c2 [50] , *2-allele containing ALDH2 genotypes [9] , and shorter (s) allele-containing L-myc [10] genotypes. However, other studies have not found any association between gastric cancer and these genotypes [51][52][53] .…”
Section: Discussion Discussion Discussion Discussion Discussionmentioning
confidence: 99%
“…Genetic polymorphisms of xenobiotic-metabolizing enzymes can also affect susceptibility to cancer. Several studies have reported that the genetic polymorphisms of metabolic enzymes, such as cytochrome p450 2E1 (CYP2E1) [5] , glutathione S-transferase mu 1 (GSTM1) [6] , glutathione Stransferase theta 1 (GSTT1) [7] , aldehyde dehydrogenase 2 (ALDH2) [8] , and L-myc proto-oncogene [9] , and mutations of p53 [10] and Ki-ras [11] genes are associated with the development of gastric cancer.…”
Section: Introduction Introduction Introduction Introduction Introducmentioning
confidence: 99%
“…For example, a considerable number of investigations indicate that individuals with a homozygous deletion of the GSTM1 gene (GSTM1 null genotype) are susceptible to lung and urinary bladder cancers [1,3,5]. However, the link between the GSTM1 polymorphism and gastric carcinoma is controversial [6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%